2000
DOI: 10.2131/jts.25.3_167
|View full text |Cite
|
Sign up to set email alerts
|

Studies on thyroid function in rats subjected to repeated oral administration with kojic acid.

Abstract: To elucidate the effects of kojic acid on thyroid function, the compound was given orally to male rats for 4 weeks at 0, 4, 15, 62.5, 250 and 1,000 mg/kg. In 1,000 mg/kg treatment of kojic acid, the rats showed a slight decrease in motility, inhibition of body weight gain, and a decrease in food consumption. An increase in thyroid weight and a morphological change, i.e., hypertrophy of epithelial cells of the thyroid gland follicles, were observed after 1 week of administration. In addition, the uptake of radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 6 publications
2
9
0
Order By: Relevance
“…Histopathologically, decreased colloid in the follicles, and hypertrophy/diffuse hyperplasia were apparent in this group 13 . Inhibition of iodine uptake and organic iodine formation in the thyroid gland by kojic acid have also been recently reported by others 14,15 .…”
Section: Methodssupporting
confidence: 75%
“…Histopathologically, decreased colloid in the follicles, and hypertrophy/diffuse hyperplasia were apparent in this group 13 . Inhibition of iodine uptake and organic iodine formation in the thyroid gland by kojic acid have also been recently reported by others 14,15 .…”
Section: Methodssupporting
confidence: 75%
“…Recently, we have also reported thyroid weight gain and a morphological change, i.e., follicular epithelial hypertrophy, observed in the thyroid of rats orally administered KA for 4 weeks (Higa et al, 2000). In addition, increased 125 I uptake from blood into the thyroid was observed along with increased 125 I in the TCA-precipitation fraction in the thyroid gland.…”
Section: Introductionmentioning
confidence: 69%
“…In our previous study of oral administration for 4 weeks, in which rats were given 0, 4, 15, 62.5, 250 and 1,000 mg/kg of KA, we reported that the weight increase in the thyroid gland and a morphological change, i.e., hypertrophy of the thyroid follicular epithelial cells, were observed in the group given 1,000 mg/kg of KA (Higa et al, 2000). In addition, 125 I uptake from blood into the thyroid and the 125 I in the TCA-precipitate fraction in the thyroid were enhanced in those rats, while 125 I organification activity did not change.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…With regard to carcinogenicity, despite some positive results in rodent thyroid, it was strongly indicated that thyroid carcinogenesis was due to negative feedback of the pituitary−thyroid axis following the inhibition of thyroxine synthesis caused by interference with iodine uptake and its organification due to a non-genotoxic mechanism (Higa et al, 2000;Tamura et al, 2001;Hirose et al, 2001;Higa et al, 2002;Tamura et al, 2006). On hepatocarcinogenesis, there were no findings suggesting carcinogenicity in mouse up to 1% KA treatment (unpublished data).…”
Section: Introductionmentioning
confidence: 99%